2022
DOI: 10.3390/foods11121733
|View full text |Cite
|
Sign up to set email alerts
|

Co-Application of 1-MCP and Laser Microporous Plastic Bag Packaging Maintains Postharvest Quality and Extends the Shelf-Life of Honey Peach Fruit

Abstract: Honey peach (Prunus persica L.) is highly nutritious; it is an excellent source of sugars, proteins, amino acids, vitamins, and mineral elements. However, it is a perishable climacteric fruit that is difficult to preserve. In this study, “Feicheng” honey peach fruit was used as a test material to investigate the synergistic preservation effect of 1-methylcyclopropene (1-MCP) and laser microporous film (LMF). The peach fruits were fumigated for 24 h with 2 μL L−1 1-MCP, then packed in LMF. In comparison with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Li et al . (2022) demonstrated that laser microporous plastic bag packaging for honey peaches effectively controlled the weight loss rate, maintaining it at approximately 10% by the end of storage. Liguori et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Li et al . (2022) demonstrated that laser microporous plastic bag packaging for honey peaches effectively controlled the weight loss rate, maintaining it at approximately 10% by the end of storage. Liguori et al .…”
Section: Discussionmentioning
confidence: 99%
“…Li et al . (2022) reported a similar result regarding the improvement of shelf life and postharvest quality of peach fruit through the co‐application of 1‐MCP and laser microporous plastic bags.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1-MCP treatment 1-MCP is a highly effective ethylene inhibitor that competes irreversibly with ethylene for receptor binding sites and inhibits the role of ethylene in promoting ripening and senescence in fruits and vegetables. 27,[92][93][94] As a respiratory leap type of edible mushroom, the postharvest physiological metabolism of the golden mushroom is vigorous, and the rate of quality deterioration is closely related to the amount of ethylene released (Fig. 2 and Table 2).…”
Section: Antibacterial Cleaningmentioning
confidence: 99%